APA Handbook of Sport and Exercise Psychology, Volume 1: Sport Psychology (Vol. 1). 2019
DOI: 10.1037/0000123-009
|View full text |Cite
|
Sign up to set email alerts
|

Youth sport: Meeting unique development needs of young athletes for preventing dropout.

Abstract: Researchers from sport psychology and, more recently, the broader field of youth 1 development have been interested in understanding and identifying ways that youth sport can facilitate positive youth development. There are many reasons for adults' interest in youth sport. First, youth sport participation is pervasive, with millions of children involved in the United States and throughout the world National Council of Youth Sports, 2008). Second, sport is viewed as an activity in which children voluntarily p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…I’m done with soccer.” Like the decision for me not to be on their team, when I got cut…It really took a mental toll on me and I almost decided to quit.In this excerpt, Shania articulates how not making her high school team served as a fragmenting point for her own interpretation of her athleticism in comparison with her peers. Tryouts can be particularly problematic for girls as they are trying to establish and maintain other positive identities as they transition into high school (Gould & Walker, 2019). Reduced or little playing time on a team can also fragment girls’ athletic identity, given that they are unable to publicly enact this identity by contributing to the success of the team.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…I’m done with soccer.” Like the decision for me not to be on their team, when I got cut…It really took a mental toll on me and I almost decided to quit.In this excerpt, Shania articulates how not making her high school team served as a fragmenting point for her own interpretation of her athleticism in comparison with her peers. Tryouts can be particularly problematic for girls as they are trying to establish and maintain other positive identities as they transition into high school (Gould & Walker, 2019). Reduced or little playing time on a team can also fragment girls’ athletic identity, given that they are unable to publicly enact this identity by contributing to the success of the team.…”
Section: Resultsmentioning
confidence: 99%
“…At first, it may appear that many of the fragmenting athletic identity turning points participants described would be similar for boys transitioning into high school (e.g., injury, negative coach interactions, reduced playing time, decreased social relationship time). Mixed-sex studies have documented similar reasons among male and female youth athletes discontinuing sport, including a lack of parental support, low coach-athlete relationship quality, low enjoyment, and low peer acceptance (Gardner et al, 2017; Gould & Walker, 2019). However, past research has also found differences in self-reported reasons regarding sport participation among male and female athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversifying the voices contributing to youth sport scholarship could be beneficial to scholars seeking to help improve community sport programs in North America, which although popular, also face high rates of attrition (Fehr, 2011; Gould & Walker, 2019). We urge proponents of positive youth development programs to consider the role ALL youth could play in determining culturally relevant life skills which are based on their current needs and social realities.…”
Section: Discussionmentioning
confidence: 99%
“…Integration, as conceptualized and regarded as an optimal form of acculturation by postpositivist researchers, is a shared process of learning through which individuals remain connected with their ethnic (i.e., home) cultural norms while adapting to the cultural norms of those they interact with (Berry, 2019). However, the onus is often placed on forced immigrant youth to change the way they engage in sport to fit the sport programs available in the host community due to an assumption on the part of program administrators and coaches that all youth enter into sport for similar reasons (Jeanes et al, 2015), such as a desire for individual success and development (Gould & Walker, 2019). A lack of appreciation for culturally infused reasons for sport participation can lead to the expectation forced immigrants will navigate and participate in existing sport programs without support from host community members (Jeanes et al, 2015; Spaaij, 2015).…”
mentioning
confidence: 99%